Gettysburg [videorecording (DVD)] - Maxwell, Ronald F.; Berenger, Tom, 1949-; Daniels, Jeff, 1955-; Sheen, Martin; Elliott, Sam, 1944-; Caulfield, Maxwell; Conway, Kevin; Howell, C. Thomas, 1966-; Jordan, Richard, 1937-1993; Lang, Stephen, 1952-; Oostrum, Kees van, 1953-; Edelman, Randy; et al. (Warner Home Video, 2010)
This Civil War drama depicts the events and personal struggles of the Union and Confederate soldiers at the Battle of Gettysburg.